FACTORS AFFECTING CUSTOMER SATISFACTION AT KAHYANGAN COFFEE AND EATERY MADIUN - Salsabila, Aina; Winarno, Sri Tjondro; Setiawan, Risqi Firdaus (Universitas Islam Kadiri, 2026)
The growth of coffee shop businesses in Indonesia, including in Madiun, shows increasingly fierce competition as people's lifestyles evolve in terms of choosing places to socialize and enjoy coffee products. This situation presents both opportunities and obstacles for entrepreneurs to continuously innovate. This research aims to examine the factors influencing customer contentment. at Kahyangan Coffee and Eatery Madiun. This study seeks to investigate the elements that contribute to customer satisfaction at Kahyangan Coffee and Eatery Madiun. A quantitative methodology was applied using accidental sampling, involving 100 respondents aged at least 15 years who had made at least two purchases. Information was gathered employing a survey instrument and subsequently evaluated using the Partial Least Squares (PLS) methodology, facilitated by WarpPLS 7.0 software. The structural model evaluation was based on p-value testing and path coefficient. The research findings indicate that price perception has a positive and significant correlation with customer satisfaction (p-value<0.05; path coefficient=0.234). Similarly, location shows a significant positive effect (p-value<0.001; path coefficient = 0.402), product quality has a significant positive impact (p-value = 0.012; path coefficient = 0.216), and service quality also has a significant positive influence (p-value = 0.002; path coefficient = 0.281). This study offers practical implications for Kahyangan Coffee and Eatery in optimizing its marketing and operational strategies to increase customer satisfaction levels in a competitive coffee shop industry environment.